The legal basis for the liability of the oil operator for the actions of his subordinate - Zubair Mustafa Hussein; Dastan Muhammad Aziz (The Scientific Journal of Cihan University– Sulaimaniya, 2018)
The performer of oil operations uses many people to carry out the oil operations, and that is because of the multiple stages of the oil operations and the complexity and the expansion of the oil operations. Undoubtedly, the implementation of these operations by the parties does not prevent the occurrence of the damage. Damage caused by its users, which raises serious questions about determining the basis for the liability of the performer of oil operations for the actions of its subsidiary. Based on the above, we intended to address this issue through two sections: In the first section, we decided to define the terms of liability of the performer of oil operations for the work of its subordinates, through three subsections, we have assigned each subsections to research the terms of liability. And, in the second section we discussed the basis of the responsibility of the performer of oil operations for the work of its subordinates, which includes two subsections, the first subsection deals with the basis of the responsibility of the performer of oil operations for the work of its subordinates according to the opinions of jurists. In the second section, we discussed the basis of the liability of the performer of oil operations for the work of its subordinates in comparative legislations. In the course of our research on the subject matter, we reached several conclusions, the most important of which is that in order to realize the liability of the performer of oil operations for the actions of its subsidiaries , the general conditions for the liability of the person responsible for the acts of his or their subordinates should be satisfied, and that is the existence of a relationship between the person and the subordinate, and an fault occurred from the subordinate and damage to the other, and the attachment of the fault of the subordinate’s work , which includes the fault of the subordinates during or because of their employment in accordance with Libyan and Kuwaiti civil law, and includes the fault of the subordinates during their employment only in accordance with Iraqi civil law. Comparative private legislation, such as the Oil and Gas Act and the Environmental Protection and Improvement Act, did not address the responsibility of the person (the performer of oil operations) for the acts of his subordinate, except for the Protection and Environment Improvement Act for Kurdistan and Iraq, as well as Iraq, on this basis, and established on the basis of assumed liability. Referring to the general rules contained in the Civil Code, it is clear to us that the basis of the liability of the person for the acts of his subordinate in Iraqi civil law is a presumed error and able to prove the opposite, and the Libyan and Kuwaiti civil codes do not address this issue.